An LRR-only protein promotes NLP-triggered cell death and disease susceptibility by facilitating oligomerization of NLP in Arabidopsis - Chen, Jun-Bin (The New phytologist, 2021)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.